A Critical Analysis of Handbook of College Teaching - Hossein Abdollahi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to criticize and analyze the content and structure of “the Handbook for College Teaching”. The research method was a critical exploration. The book has been criticized and analyzed in terms of its form (advantages and shortcomings) as well as its content (intra-structure). The main positive points of the book are simple and fluent prose, expressing the objectives of the book, using simple and technical terms, presenting conceptual prerequisites, expressing the disadvantages and benefits of teaching methods. However, the negative points are its emphasis on traditional methods and its ignorance of the new teaching methods. The authors did not make a distinction between the concepts of teaching methods, techniques, and skills. There is no appropriate cohesion among the titles within the chapters. Instructional objectives are not mentioned at the beginning of each chapter. Only a few pictures and images were used to help the learners understand the text. Critical thinking methods and techniques, as an integral component of higher education, were, to a great extent, neglected. The theoretical background and the literature of the related studies do not meet academic book expectations. At the end of the article, suggestions are made to improve the content of the book.